PEMAHAMAN DESAIN PEMBELAJARAN IPA BERBASIS POE MODEL DAN DAMPAKNYA TERHADAP KARAKTER SISWA SEKOLAH DASAR - Hidayat, Arif; Sofi Mutiara Insani; Syarif Hidayat; Sima Mulyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research describes the understanding of Poe Model-based science learning design and its impact on the character of elementary school students. The purpose of the research conducted is to identify and understand how the application of the POE learning model can affect the development of student character and to evaluate the effectiveness of the model in the context of science learning in elementary school. The research method used was descriptive qualitative with data collection through observation, interviews and documentation with the research subjects being 85 students at SDN 3 Golat. Data analysis techniques were carried out through data collection and conclusion drawing. The results showed that understanding the POE model in science learning was effective in developing student characters, such as curiosity, cooperation, responsibility, and independence.Teacher training and infrastructure support are needed to optimize results. Integration of POE in the curriculum, periodic evaluation, and further research are suggested to improve learning effectiveness and student character development.